RELATIONSHIP BETWEEN THE THIGH ANTHROPOMETRIC MEASUREMENTS WITH ISOKINETIC PERFORMANCE OF KNEE MUSCLES (International Journal of Physiotherapy, 2020)
Background: Strength measurement is an essential component of assessment in rehabilitation. However, there may be many factors that may alter muscle performance, among which anthropometric values play a significant role. Therefore, the objective of this study is to find out the correlation between thigh anthropometric measurements with the knee isokinetic muscle performance.Methods: Eighteen young, healthy male adults, whose mean age was of 21.22 ± 1.39 were included. Anthropometric measurements like height, weight, thigh girth, and femoral length were correlated with isokinetic strength of knee flexor and extensor muscles. The variables collected in isokinetic measurements; used for analysis were peak torque at three angular velocities of 60°/s, 120°/s, and 180°/s.Results: The Pearson correlation between the thigh girth and isokinetic peak torque at angular velocities of 600/s, 1200/s, and 1800/s for knee extensors were, r = 0.52, 0.69 and 0.73 whereas for knee flexors it was r = 0.53, 0.24 and 0.44 respectively which showed moderate to high correlation when the level of significance was kept at 0.05. However, the correlation between the femoral length and isokinetic peak torque at three angular velocities for knee muscles showed a weak positive correlation only.Conclusion: Study results show that there is a moderate to strong positive correlation exists between thigh girth and isokinetic peak torque of knee musculature, whereas there is only a weak correlation exists between femoral length and isokinetic peak torque of knee musculature. Therefore, it reveals that the length of the extremity does not seem to influence the outcome of isokinetic measurement values. In contrast, the girth of the muscle can influence the outcome of the isokinetic measurement values, especially for the knee joint.